Pulmonary alveolar proteinosis: another autoimmune disease associated with sarcoidosis? - Boerner, Eda Burcu; Costabel, Ulrich; Wessendorf, Thomas Ernst; Theegarten, Dirk; Hetzel, Martin; Drent, Marjolein; Bonella, Francesco (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Pulmonary alveolar proteinosis (PAP) is a rare lung disease characterized by the accumulation of surfactant phospholipids and lipoproteins within the alveoli.  Here we report on a female patient who was diagnosed with autoimmune PAP and successfully treated with whole lung lavage (WLL). 15 months after PAP diagnosis the patient developed marked fatigue. Additional tests revealed the diagnosis of sarcoidosis. We can only speculate that PAP and sarcoidosis in our patient are linked to each other based on the fact that other autoimmune disorders have also been associated with sarcoidosis.